STRATEGI KOMUNIKASI PEMASARAN DIGITAL SITUS PEMBANDING HARGA TELUNJUK.COM - Nursatyo Nursatyo; Dini Rosliani (President University, 2018)
Abstract. The development of E-commerce in Indonesia has made the actors of digital industry create a price comparison site to help prospectice customers to make decisions in making a purchase. The existence of this price comparison business requires a marketing communication stratey than does not only make effort to draw the interest of the Internet users to visit to the site, but also on how to draw the attention of the online sellers and for them to cooperate. This article presents a digital marketing communication strategy of one of the price comparing websites in Indonesia, telunjuk.com, to increase their traffic. The research method used is the descriptive qualitative research method. Data were collected by interviewing key personnels at telunjuk.com i.e., Chief Marketing Officer as the the key informant and Digital Marketing Specialist as informant 1, and Content Specialist as informant 2. Besides that, the authors performed observations on the other price comparison sites and E-commerce sites through the internet media. The authors also performed a thorough rebiew of relevan print media. The result shows that the digital marketing communication strategy implemented by telunjuk.com in improving traffic is done through adding display advertising, SEM and SEO search engine optimization, and community platforms. Keywords: Digital Marketing Communication, Price comparison Sites